Limit periodic perturbations of difference systems with coefficients from commutative groups. Issue 1 (2nd January 2023) - Hasil, Petr; Veselý, Michal
Abstract : We study perturbations of homogeneous linear difference systems over infinite fields with absolute values. The coefficient matrices of the treated systems belong to commutative groups which do not need to be bounded. We present a general limit periodic transformation of an arbitrarily given system such that the obtained system has non-almost periodic solutions. We also formulate corollaries which show how the presented construction of the perturbed system improves and extends known results.